Risk and Resilience in LGBTQ Youth : a Critical Review of the Suicide and Self-Injury Literature - Quigley, Katherine E. (My University, 2012)
Self-injury and suicide have been found to be prevalent in adolescent populations (e.g., Jacobson & Gould, 2007). At increased risk within these populations are youth who identify as lesbian, gay, bisexual, transgender or queer/questioning, or LGBTQ (e.g., Deliberto & Nock, 2008). This study looked at the critical review of the empirical literature examining factors linked to increased suidical behavior and non-suicidal self-injury among LGBTQ teens, as well as resilience factors protecting against self-harm.
Color poster with text, images, and charts.
Keywords: Sexual minority youth; Suicide; Self mutilation; Posters